Control of Gadget Addiction Among Children: Analysis from an Islamic Perspective in the Digital Age - Ismail, Faisal Bin Husen; Destari, Dina; Ahmad, Shakila Binti; Mohd Khalid, Halimi Binti; Syed Abu Bakar, Sharifah Khadijah Binti (Fenomena, 2023)
In the era of globalization, gadgets have become a hot topic everywhere, even across the globe. Gadgets have become a widespread possession for everyone, regardless of age. This research will focus on the effects of gadget usage on children and identify ways to control gadget usage among children in Malaysia from an Islamic perspective. The research methodology employs a descriptive qualitative approach, referring to books, journals, and newspaper articles as primary references. Additionally, the secondary data for this study includes a questionnaire related to gadget addiction among children, which 325 respondents answered. The study found that the highest percentage of children playing with gadgets is 2 to 3 hours daily. Furthermore, it revealed that YouTube is children's most frequently viewed social media platform. Regarding time distribution, 39 percent reported having no time control when using gadgets. The research also found that gadgets cannot strengthen family relationships, as indicated by 86.5 percent of the respondents. All parties should take this issue seriously in regulating children's gadget use. It is crucial to address this matter early on to prevent adverse effects on children in the future.